CRISPR/Cas12a‐mediated genome engineering in the photosynthetic bacterium Rhodobacter capsulatus. Issue 6 (27th March 2021) - Zhang, Yang; Yuan, Jifeng
Summary: Purple non‐sulfur photosynthetic bacteria (PNSB) such as Rhodobacter capsulatus serve as a versatile platform for fundamental studies and various biotechnological applications. In this study, we sought to develop the class II RNA‐guided CRISPR/Cas12a system from Francisella novicida for genome editing and transcriptional regulation in R. capsulatus . Template‐free disruption method mediated by CRISPR/Cas12a reached ˜ 90% editing efficiency when targeting ccoO or nifH gene. When both genes were simultaneously edited, the multiplex editing efficiency reached > 63%. In addition, CRISPR interference (CRISPRi) using deactivated Cas12a was also evaluated using reporter genes egfp and lacZ, and the transcriptional repression efficiency reached ˜ 80%. In summary, our work represents the first report to develop CRISPR/Cas12a‐mediated genome editing and transcriptional regulation in R. capsulatus, which would greatly accelerate PNSB‐related researches. Abstract : CRISPR/Cas12a‐mediated genome editing was developed in purple non‐sulfur photosynthetic bacteria; CRISPR interference based on deactivated Cas12a was established in purple non‐sulfur photosynthetic bacteria; CRISPR/Cas12a‐mediated genome editing/transcriptional repression would greatly accelerate in purple non‐sulfur photosynthetic bacteria related biotechnological applications.